Risomania the new spirit of printing - Komurki, John Z. (Niggli, 2017)
"Risomania is the first book to document and discuss this groundbreaking global scene, looking at the histoy, present and future of the Riso, as well as featuring a range of artists, design studios and print shops who use it. At the heart of the volume are fabulous, hugely diverse examples of Riso-printing, including postcards, magazines, posters, flyers, and experimental printed products, all of which inspire through vivacity of colour, unique textures and, above all, the perfectly imperfect authenticity of Risography."-- Back cover "Risography, named after the Japanese firm Riso, is a stencil printing process based on screen printing techniques that was developed in the transition phase from mechanical to digital printing. Although the printer looks like a copying machine, the colors are transferred onto the paper without the use of heat or chemicals, saving energy and making the process ecologically friendly. Graphic artists and designers from around the world have now rediscovered the risograph for themselves - along with other machines for similar, almost forgotten techniques such as mimeography - and sparked an unexpected renaissance of analog printing. A comprehensive introduction that addresses past, present and future is followed by an essay about the key pioneers in the contemporary risography scene. In the chapter 'Risoworld' notable risography-oriented publishers, printers and design studios from around the world are presented. At the heart of the book are fabulous, hugely diverse examples such as postcards, magazines, posters, flyers and experimental printed products, all inspired by the force of their color, their unique textures and, above all, the perfectly imperfect authenticity of risography."--From publisher's website